Sustainable construction use of incinerator ash : proceedings of the international symposium organised by the Concrete Technology Unit, University of Dundee and held at the University of Dundee, UK on 20-21 March 2000 - Dhir, Ravindra K.; Dyer, Thomas D.; Paine, Kevin A. (Thomas Telford, 2000)
This title is the proceedings of the major international workshop that took place at the University of Dundee. Papers are included by experts in the field of sustainable construction showing developments in the processing and use of incinerator ash in the construction industry.
Keywords: Construction industry -- Environmental aspects -- Congresses.; Concrete -- Environmental aspects -- Congresses.; Waste products as building materials -- Congresses.; Incineration -- Environmental aspects -- Congresses.; elektronické knihy; electronic books